Síntese e aplicação do SrTiO3 na fotodecomposição da água para a geração de hidrogênio - Pinheiro, Antônio Narcisio (Universidade Federal de São Carlos, 2014)
Strontium titanate (SrTiO3) is an n-type semiconductor with high chemical and photochemical stability. This wide band gap oxide has a band gap energy of about 3.2 eV as well as a favorable energy for photocatalysis. In this study, we demonstrate an alternative and superior method to produce Nb-doped and undoped SrTiO3 photoanode thin films based on a colloidal deposition process which possess good activity under standard solar illumination conditions. Methanol was used as hole scavenger and the results showed that the semiconductor liquid junction (SCLJ) charge accumulation is not an important mechanism to control the photocurrent density and overpotential. In addition, experimental results suggest that the dominance of photocurrent density is controlled by the potential at the surface space charge layer for the Nb-doped SrTiO3 and by recombination at the depletion layer for the undoped oxide.
Synthesis and application of srtio3 photodecomposition in water for hydrogen generation
Keywords: Fotocatálise; Titanato de estrôncio; Fotodecomposição; Fotoanodos; Filmes finos; Hidrogênio; CIENCIAS EXATAS E DA TERRA::QUIMICA